2020
DOI: 10.1515/ijcre-2020-0179
|View full text |Cite
|
Sign up to set email alerts
|

The electrochemical reduction mechanism of Fe3O4 in NaCl-CaCl2 melts

Abstract: In order to study the process of Fe3O4 reduction by melt electro-deoxidation. Electrochemical method was used to analyze the reduction mechanism of Fe3O4 in NaCl-CaCl2 melts. The effects of cell voltage and time on the product were discussed through constant cell voltage electrolysis. The results showed: (1) The reduction of solid Fe3O4 to metallic Fe is a two-step process for obtaining electrons. (2) The transformation process (600 min, 0–1.0 V) of the electrolysis products with the increase of the cell volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In comparison to the MOE method, this process achieves the direct electrolytic production of metals and alloys at lower temperatures ranging from 800 • C to 850 • C [19,20]. The use of solid metal oxides as cathodes in chloride molten salts for a direct electrochemical reduction to produce elemental metals has been applied in the extraction of various metals, including Fe [21,22], Ti [23], Cr [24,25], Al [26], V [27,28], Se [29], titanium-based [30][31][32][33][34], aluminum-based alloys [35,36], high-entropy alloys [37], etc. Research has shown that the addition of a small amount of CaO to CaCl 2 can significantly increase the rate of reduction and deoxidation [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the MOE method, this process achieves the direct electrolytic production of metals and alloys at lower temperatures ranging from 800 • C to 850 • C [19,20]. The use of solid metal oxides as cathodes in chloride molten salts for a direct electrochemical reduction to produce elemental metals has been applied in the extraction of various metals, including Fe [21,22], Ti [23], Cr [24,25], Al [26], V [27,28], Se [29], titanium-based [30][31][32][33][34], aluminum-based alloys [35,36], high-entropy alloys [37], etc. Research has shown that the addition of a small amount of CaO to CaCl 2 can significantly increase the rate of reduction and deoxidation [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21] Unfortunately, not all the metal oxides, including SnO 2 , can find a suitable IL or DES for dissolution. It has been shown that such solubility problem can be bypassed by direct cathodic electrolysis of solid metal oxides such as TiO 2 , 22,23 Fe 3 O 4 , 24 NiO, 25 SnO 2 , 26 and NiO/ZrO 2 27 to their metal state in higher temperature molten salts such as CaCl 2 , 22,23,25 NaCl-CaCl 2 , 24 LiF-NaF, LiF-CaF 2 26 and LiCl. 27 From these studies, it is generally recognized that the oxygen in the metal oxides, M x O y , was ionized upon the transfer of electron to the metal oxide at the cathode according to: M x O y(s) + 2ye − = xM (s) + yO 2− .…”
mentioning
confidence: 99%